Under Which Conditions Can Older Participants Maintain Information In Working Memory?. Issue 5 (20th October 2017) - Plancher, Gaën; Boyer, Hélène; Lemaire, Benoît; Portrat, Sophie
ABSTRACT: Background/Study Context : Age-related deficits in working memory (WM) are commonly described in the literature. However, age-related deficits in WM maintenance mechanisms have received less attention. Based on recent models of WM, the present study aims at determining the conditions under which older adults are able to maintain information. More precisely, we wondered whether the cognitive load effect, taken as evidence for active maintenance in WM, is observed in normal aging and whether it interacts with the level of interference of a concurrent task. Methods : Young (mean age = 21.62; SD  = 2.51) and healthy older (mean age = 71.92; SD  = 5.18) participants performed a complex WM task. They had to remember five images while reading three words presented after each image. We compared trials in which every word was new (inducing high interference) with trials where words were repeated (inducing low interference). The pace at which the reading task was performed was either fast or slow, resulting in a high or a low cognitive load. Results : As suggested in the literature, young participants presented better performance at slow pace compared with fast pace but were not influenced by interference. Older participants also performed better at slow pace but only when interference was low. Interestingly, the older population showed negative correlations between slow-pace trials and switching abilities. Finally, although computational simulations with time-based resource sharing* (TBRS*) provide a good fit for young adult performance, several parameters had to be adjusted to fit the older participants' performance, including duration of trace refreshing. Conclusion : Our findings suggest that a decrease in WM performance with aging can be explained by a difficulty in taking advantage of WM maintenance opportunities, especially in conditions of high interference. The computational investigations are consistent with this interpretation given that the parameters to be adjusted involve maintenance in WM. Finally, the computational approach seems a relevant way to address causes of forgetting in aging.